MEMBANGUN HEALTH-PRENEURSHIP BAGI MAHASISWA KEDOKTERAN DAN KEDOKTERAN GIGI UNIVERSITAS HANG TUAH SURABAYA - Ghita Hadi Hollanda; Indarti; Edi Pratiknya D (Universitas Hang Tuah Surabaya, 2022)
The introduction of entrepreneurship is expected to change the mindset of students to aspire to become entrepreneurs, not just ambitions to become Civil Servants (PNS). This understanding must be started while still a student. Entrepreneurship education is beneficial in providing provisions before medical faculty and dentistry faculty students will later become doctors or dentists. This entrepreneurship development program can be implemented as a